Effect of plant density on soluble carbohydrates and ascorbic acid contents of cauliflower (Brassica oleracea cv. botrytis) - Gutierrez, Luiz Eduardo; Minami, Keigo; Katayama, Massar; Silva, Ilene R. da; César Jr., Wilson P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Total soluble carbohydrates, glucose, fructose, sucrose and ascorbic acid contents were determined in cauliflower (Brassica oleracea CV. botrytis) samples. The effect of plants densities was studied in this paper. Statistically differences were not observed amoung treatments, although the samples from 20633 plants/ha showed higher level of ascorbic acid. Dry weight varied from 8.24 to 10.13% and ascorbic acid contents varied from 93.1 to 113.5 mg/100 g fresh weight basis. Soluble carbohydrates, in g/100 g fresh weight basis, were: total (3.17-4.54), sucrose (0.26-0.66), glucose (0.92-1.50) and fructose (0.91-1.45).